Business Cycles in Small Developed Economies : The Role of Terms of Trade and Foreign Interest Rate Shocks - Guajardo, Jaime (Washington, D.C. : International Monetary Fund, 2008)
Empirical evidence for small developed economies finds that consumption is procyclical and as volatile as output, and real net exports are coutercyclical. Earlier studies have not been able to reproduce these regularities in a DSGE small open economy model when productivity shocks drive the business cycles and households have a normal intertemporal elasticity of substitution. Instead, these studies have reduced this elasticity to make consumption more procyclical and volatile and real net exports countercyclical. This paper shows that a standard model can reproduce these regularities, without lowering the intertemporal substitution, if the terms of trade and foreign interest rate are added as source of business cycle fluctuations. These shocks, compared to productivity shocks, make consumption and investment more volatile and procyclical relative to output, and make real net exports countercyclical.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet